Fecal Microbiota Transplantation Controls Progression of Experimental Autoimmune Hepatitis in Mice by Modulating the TFR/TFH Immune Imbalance and Intestinal Microbiota Composition - Liang, Ma; Liwen, Zhang; Jianguo, Song; Juan, Dai; Fei, Ding; Yin, Zhang; Changping, Wu; Jianping, Chen (Frontiers in Immunology, 2021)
Intestinal microbiota (IM) dysbiosis contributes to the development of autoimmune hepatitis (AIH). This study aimed to investigate the potential effect of fecal microbiota transplantation (FMT) in a murine model of experimental AIH (EAH), a condition more similar to that of AIH patients. Changes in the enteric microbiome were determined in AIH patients and EAH mice. Moreover, we established an experimental model of secondary EAH mice harboring dysbiosis (ABx) to analyze the effects of therapeutic FMT administration on follicular regulatory T (TFR) and helper T (TFH) cell imbalances and IM composition in vivo. Alterations of the IM composition and bacterial translocation occurred in AIH patients compared to nonalcoholic fatty liver disease patients and healthy controls (HCs). Therapeutic FMT significantly attenuated liver injury and bacterial translocation and improved the imbalance between splenic TFR cells and TFH cells in ABx EAH mice. Furthermore, therapeutic FMT also partially reversed the increasing trend in serum liver enzymes (ALT and AST) of CXCR5−/−EAH mice on the 28th day. Finally, therapeutic FMT could effectively restore antibiotic-induced IM dysbiosis in EAH mice. Taken together, our findings demonstrated that FMT was capable of controlling hepatitis progression in EAH mice, and the associated mechanism might be involved in the regulation of the TFR/TFH immune imbalance and the restoration of IM composition.